Penataan Pasar Tradisional sebagai Pusat Aktvitas Ekonomi dan Relasi Sosial di Kota Ambon - Simon Pieter Soegijono (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2022)
Abstract — Traditional markets are one of the most tangible indicators of community economic activity in an area. The market is one of the public facilities whose existence supports the economic activities of the community. The market is a communication medium for everyone's encounter without limits. The existence of the market should be a place that provides comfort for its users. However, in reality, traditional markets have received almost no attention. This research was conducted to study the arrangement of traditional markets. With qualitative research methods and survey research types, it is hoped that it will answer the needs of traditional market arrangements by the Ambon City Government.Keywords: market, social relations